FEATURES OF APPLICATION OF PROGRAMMED LOGICAL OF INTEGRATED CIRCUITS FOR IMPLEMENTATION OF PCI CONTROLLER INTERFACE - Pashchenko, N. V. (Problems of Informatization and Management, 2005)
The article analyzes the opportunities provided to modern developers to implement their solutions using the PCI bus. Alternatives and cost characteristics of existing approaches are considered. The main advantages of FPGA mwty FPGA in the implementation of the PCI interface controller are given.